Performance analysis of dividing wall column model for fractionation of oleochemical fatty acid - Mohamad Rizza, Othman; Rangaiah, Gade Pandu (Malaysian Palm Oil Board, 2020)
Fractionation process of oleochemical products in Malaysia normally uses conventional distillation columns (CDC). Due to the considerable amount of energy used in the separation process, there is a need to have an intensified process. Dividing wall column (DWC) is an attractive option which offers big advantages with reduced cost and energy consumption. However, research on its feasibility for oleochemical fractionation is scarce. In this article, we conducted a model-based performance analysis of DWC for oleochemical fatty acid fractionation. The model was designed and simulated using a customised four column configurations in Aspen Plus. A step-by-step design procedure was introduced to aid the model development. Economic and environmental assessment was performed and compared with conventional distillation columns. Hydraulic analysis of several packing type was also performed to gain insights on the column hydrodynamic behaviour. Our result shows that the major economic advantage is in the operating cost with savings of up to 16.9% and 10.2% on cooling and heating utilities, respectively while reduces 10.2% of CO2 emissions. Overall, our study shows the feasibility of fractionating fatty acids in oleochemical industry using DWC. Such assessment is important to assess its feasibility especially during the early stage of technology development prior to industrial implementation.